High-performance dual-band frequency-selective rasorber based on cascaded metasurface - Li, Qiushi; Li, Xiaotong; Chen, Yanrui; Ding, Fan; Chen, Cong; Liu, Huanhuan; Xiao, Shiyi (Frontiers in Materials, 2022)
Frequency-selective rasorbers (FSRs), which have absorptive and transmissive properties at different frequencies, are crucial in a wide range of applications in communication and radar engineering. However, the FSRs currently available usually exhibit a single high-performance transmission band, which cannot meet the rising demands for modern multi-band communication/radar systems. In this paper, we propose a dual-band frequency-selective rasorber that utilizes a cascaded metasurface and is designed with an equivalent circuit model and parameter optimization. Besides, a prototype dual-band frequency-selective rasorber is fabricated and characterized. Microwave measurements present two highly transparent peaks located near 11.5 GHz and 17.5 GHz with an insertion loss of around 0.5 dB. Also, there are two absorption bands with absorptivities higher than 80% at 3.9-10.2 GHz and 13-15 GHz. Such low insertion loss for both transparent bands is achieved by optimizing the position of resistors through mode analysis Our approach facilitates the manufacture of high-performance multi-band frequency-selective rasorbers for use in multi-band communication systems.